Examining the Legality of Surrogacy in Pakistan: An Analytical Perspective of Islam - Rana, Anwar; Gujjar, Muhammad Waqas; Manzoor, Bakhtawar; Akram, Hassan; Ahmad, Muhammad (Law and Policy Review, 2024)
The practice of surrogacy is prevalent worldwide, but it has yet to gain recognition in Pakistan. This study aims to explore the potential for recognizing surrogacy in Pakistan, examining its current status and the reasons it has been largely ignored. As a country founded on Islamic ideology, the practice of surrogacy needs to be justified according to the injunctions of the Holy Quran and Sunnah. This study explores whether the traditions of surrogacy in Abrahamic religions provide any jurisprudential grounds for its implementation in Pakistan. It also discusses the impact of increasing practice of surrogacy in other jurisdictions on Pakistan’s legal system. To understand why there is lack of recognition and legislation regarding surrogacy in Pakistan, this study critically analyzes its societal and cultural acceptance in the context of Islamic society. It examines reasons why surrogacy is treated as a taboo in Pakistan’s parliament and judicial system. In order to thoroughly understand these issues this study examines how the legal system in Pakistan works and how the laws are created. It critically analyses the judicial precedents in Pakistan and briefly explains its legal system to fathom the perimeters how law is created and enforced.